2020
DOI: 10.1109/access.2020.2971327
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Ant Colony Algorithm for Optimized Band Selection of Hyperspectral Remotely Sensed Imagery

Abstract: The ant colony algorithm (ACA) has been widely used for reducing the dimensionality of hyperspectral remote sensing imagery. However, the ACA suffers from problems of slow convergence and of local optima (caused by loss of population diversity). This paper proposes an improved ant colony algorithm (IMACA) based band selection algorithm (IMACA-BS), to overcome the two shortcomings of the standard ACA. For the former problem, a pre-filter is applied to improve the heuristic desirability of the ant colony system;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Ding et al [22] suggested IMCA-BS (Improved AC algorithm-based band selection) algorithm in order to solve the drawbacks of the conventional AC algorithm. In the IMACA-BS, the initialization of pheromone on each path is based on the heuristic desirability amongst each pair of nodes with the means of a pre-filter.…”
Section: Improvement By Applying Pheromones Updatementioning
confidence: 99%
“…Ding et al [22] suggested IMCA-BS (Improved AC algorithm-based band selection) algorithm in order to solve the drawbacks of the conventional AC algorithm. In the IMACA-BS, the initialization of pheromone on each path is based on the heuristic desirability amongst each pair of nodes with the means of a pre-filter.…”
Section: Improvement By Applying Pheromones Updatementioning
confidence: 99%
“…Feature extraction techniques (e.g., Principal Component Analysis and Linear Discriminant Analysis) are designed to compress data by using mathematical transformations. Due to every band of the HSI having its corresponding image, the way of feature extraction that the high-dimensional feature space is mapped to a low-dimensional space by linear or nonlinear transformation could not keep the primitive physical significance of the HSI [9]. Thus, feature extraction techniques are not suitable for the dimensionality reduction of HSIs, and so FS has been one of the effective means for solving this issue on HSIs [10], specifically by selecting the optimal subset from all the original bands to gain the desired classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the information provided by HSI is sufficient for the extraction of detailed land-use information. However, the massive bands often lead to the curse of dimensionality [4]. The classification performances of the commonly used classifiers (e.g., support vector machine (SVM) and random forest (RF)) for HSI were often limited without the reduction of feature dimensionality (e.g., feature extraction and feature selection).…”
Section: Introductionmentioning
confidence: 99%